Analisis Efektivitas Biaya Terapi Antibiotik pada Pneumonia di RSUD Sleman Tahun 2023 - Yogananda, Amrina Amalia; Faizah, Nurul; Hidayati, Listiana (Jurnal Farmasi & Sains Indonesia, 2025)
Pneumonia is an infectious disease caused by microorganisms, including viruses, bacteria, fungi, and parasites. One of the pharmacological therapies used to treat pneumonia is antibiotics. In determining antibiotics, it is necessary to select the frequency to determine the most effective and cost-effective therapy. CEA is a pharmacoeconomic method presented in the cost-effectiveness ratio to assist in drug selection decisions. This study aims to determine the most cost-effective antibiotics at Sleman Regional Hospital during 2023. Data was collected retrospectively using the medical records of pneumonia patients. The number of samples obtained was 27 patients diagnosed with pneumonia. The results showed that males suffered more from pneumonia (62.96%), the most common age was >65 years (37.04%), with a length of hospitalization of ≤5 days (70.37%). The average direct medical cost for single therapy in pneumonia patients is the largest levofloxacin of Rp 9.975.494, and the combination of oral ceftriaxone + azithromycin of Rp 14.802.488. The highest therapeutic effectiveness for single therapy is ceftriaxone at 90%, and the combination of ceftriaxone + gentamicin is 100%. Based on the ACER calculation, ceftriaxone is more cost-effective than levofloxacin for single therapy with an ACER value of Rp 86.967,94. For combination therapy, ceftriaxone + gentamicin is more cost-effective than ceftriaxone-oral azithromycin with an ACER value of Rp 61.922,26.